Peak flow based asthma self-management: a randomised controlled study in general practice. British Thoracic Society Research Committee. Issue 8 (August 1995) - Jones, K P; Mullee, M A; Middleton, M; Chapman, E; Holgate, S T
Abstract : BACKGROUND–Peak flow based asthma self-management plans have been strongly advocated in consensus statements, but convincing evidence for the effectiveness of this approach has been largely lacking. METHODS–A randomised controlled trial was conducted in 25 general practices comparing an asthma self-management programme based on home peak flow monitoring and surgery review by a general practitioner or practice nurse with a programme of planned visits for surgery review only over a six month period. RESULTS–Seventy two subjects (33 in the self-management group and 39 in the planned visit group) completed the study protocol, but diary card data for at least three months were available on a total of 84 (39 in the self-management group and 45 in the planned visit group). Teaching self-management took longer than the planned visit review. In the self-management group home peak flow monitoring was felt to be useful by doctors and patients in 28 (85%) and 27 (82%) cases, respectively. There were no between group differences during the study period in terms of lung function, symptoms, quality of life, and prescribing costs. Only within the self-management group were improvements noted in disturbance of daily activities and quality of life. Possible explanations for these negative results include small numbers of subjects, the mild nature of their asthma, and inappropriate self-management strategies for such patients. CONCLUSIONS– Rigid adherence to long term daily peak flow measurement in the management of mild asthma in general practice does not appear to produce large changes in outcomes. Self-management and the use of prescribed peak flow meters need to be tailored to individual circumstances.